The effect of age on between-match physical performance variability in professional soccer players - Lorenzo-Martínez, M.; Rey, E.; Padrón-Cabo, A. (Research in Sports Medicine, 2020)
This study aimed to analyse the effect of age on between-match variability of physical performance in professional soccer players. For this purpose, observations on entire match performance were collected on 787 professional soccer players competing in the first or second division of Spanish league during the 2017-2018 season. Players were classified into six groups according to their age: G1 (=22.5 years), G2 (22.6-25.1 years), G3 (25.2-27.5 years), G4 (27.6-30.1 years), G5 (30.2-33.1 years) and G6 (=33.2 years). Coefficients of variation (CVs) were calculated individually for each player and performance variable: total distance, low- intensity, medium-intensity, high-intensity running (HIR), sprinting, number of HIR, number of sprints, average speed and maximal speed. The main finding of this study was that players under 25.2 years (G1 and G2) showed lower CVs for high-intensity activities (HIR and sprinting) in comparison with players over 33.1 years (G6). These findings provide useful information for soccer coaches, who could put extra attention on physical performance of the oldest players when they have to play an entire match, because their performance is more variable and uncertain in comparison with the youngest.